Efeito da partícula e do momento de jateamento na caracterização superficial da zircônia e na resistência de união com cimento resinoso - Martins, Samira Branco [UNESP] (2014)
Despite Y-TZP (yttria tetragonal zirconia polycrystal) ceramic restorations became widely used in clinical practice due to its excellent properties, surface treatments are required for the improvement of the adhesion with resin cements. This study evaluated the influence of the particle and air abrasion moment on the surface characterization of a Y-TZP ceramic and its bond strength with a resin cement. Zirconia specimens were air-abraded with the following particles: 50 μm Al2O3 particles; 120 μm Al2O3 particles; 30 μm silica-coated Al2O3 particles (Rocatec Soft); and 110 μm silica-coated Al2O3 particles (Rocatec Plus). Air-abrasion was performed in 3 different moments: after zirconia sintering (AS)(control group); before zirconia sintering (BS); before and after zirconia sintering (BAS). The zirconia surface characterization including roughness (n=10), wettability (n=10), morphology (n=2) and elemental composition (n=2) was performed. The SBS test (n=11) was conducted after thermal cycling (10,000 cycles - 5ºC and 55ºC). Failure mode was determined with a stereomicroscope (×20). Roughness, wettability and SBS data were analyzed by two-way ANOVA and Tukey’s test (α=.05). For BS and BAS, the roughness increased according to the increase in the particle size. AS showed the lowest roughness, while BS and BAS did not exhibit significant difference each other. In general, Rocatec Plus and 120 μm Al2O3 particles provided the lowest and the highest contact angle. BS and BAS exhibited the highest and the lowest contact angle. The particle as well as the air-abrasion moment did not promote regular morphological patterns. The additional presence of the Si element in the groups abraded with silica-modified Al2O3 particles was the only difference observed between these groups and those abraded with Al2O3 particles. For BS, the highest and the lowest SBS was provided by 120 μm Al2O3 particles and Rocatec Soft. For BAS and AS, the highest SBS...